2017
DOI: 10.7759/cureus.1913
|View full text |Cite
|
Sign up to set email alerts
|

Using the American Association of Medical Colleges Standardized Video Interview in a Holistic Residency Application Review

Abstract: Each year, residency programs work diligently to identify the best applicants for their respective programs, given the increasing volume of applications. Interview offers are often based on a mix of subjective and objective measures, with different programs relying more or less on each. A holistic application review involves a flexible and individualized way of assessing an applicant’s capabilities through a balanced consideration of experiences, attributes, and academic metrics. When considered collectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…22 The Association of American Medical Colleges is amidst developing a standardized video interview for resident applications as an adjunct to the Electronic Resident Application Service file in order to provide program directors a holistic view of applicants rather than purely examination scores and grades. 23 Husain et al found that these standardized video interviews were more likely to increase scores of applications, leading to an in-person interview. 24 A majority of our respondents thought that an in-person interview would allow a better chance to match at that program.…”
Section: Discussionmentioning
confidence: 99%
“…22 The Association of American Medical Colleges is amidst developing a standardized video interview for resident applications as an adjunct to the Electronic Resident Application Service file in order to provide program directors a holistic view of applicants rather than purely examination scores and grades. 23 Husain et al found that these standardized video interviews were more likely to increase scores of applications, leading to an in-person interview. 24 A majority of our respondents thought that an in-person interview would allow a better chance to match at that program.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of PDs focus on academic performance and do not emphasize professionalism during the application screening, even when the information is available 18–21. PDs instead rely heavily on the residency interview to identify personality issues,22 despite its lack of sensitivity for detecting problem applicants 23…”
Section: Discussionmentioning
confidence: 99%
“…The SVI is an online, asynchronous interview designed to assess applicant proficiency in interpersonal and communication skills as well as knowledge of personal behavior. Analysis of applicant responses then provides programs with objective, standardized information about soft competencies of interest …”
Section: Innovative Methodsmentioning
confidence: 99%